Wind and solar energy potential in Herkalou and Lake Assal locations, Djibouti - Abdoulkader Ibrahim Idriss; Ramadan Ali Ahmed; Abdou Idris Omar; Hamda Abdi Atteyeh; Mohamed Houmed Ibrahim; Tahir Cetin Akinci (Institute of Advanced Engineering and Science, 2023)
The absence of meteorological data to identify the energy resources and the available energy potential represented a major obstacle in some areas in Djibouti. To solve this data problem, in this paper, wind and solar potential were assessed by collecting daily and monthly wind and solar data for the period from 1 January to 31 December 2020, for Herkalou and Lake Assal site. This study highlights that the wind resources in the Lake Assal location are falling into class 7 with high wind speed value of 16 m.s-1 and the wind energy reaching1700 kWh/m2 at 100 m height above ground level. While the Herkalou site shows a lower potential with value of 7.5 m.s-1 and 160 kWh/m2. The solar potential shows a similar distribution and a constantly high level of solar radiation throughout the year, with the monthly maximum global radiation peaks of around 900 W/m² between 11.00 and 14.00 pm for both sites. The highest monthly average of global solar irradiation values was 5.29 kWh/m2 day-1 and 6.90 kWh/m2 day-1 in March for Herkalou and Lake Assal, respectively. Results obtained in this study are favorable to deploying the solar and wind technologies for the studied sites.